The Evolution of Constitutional Regulation of Education and the New Conception in Republic of Armenia - Vagharshyan , A. (Bulletin of Yerevan University C: Jurisprudence, 2021)
The constitutional meanings of the “education”, the evolution of development of constitutional regulation of the education as a fundamental right in third republic of Armenia, the basic concepts of constitutional regulation of the right to education, and caused by these and partly existing semantic and juridical issues, the constitutional issues of the right to selfgovernment of higher educational institutions and their academic and research freedom, the encouragement of the education development as a constitutional framework and main goal of the state policy, as well as, some issues of current legislative regulations of the right to education are discussed in this article, for exposing the new conception of constitutional regulation of education’s key issues. Based on these analyses, the correction options for some constitutional tenets and concepts are proposed, as well as, the adoption of the Education Code corresponding to the new conception of constitutional regulations of the educational issues is recommended, where the public relations in the educational sector will be regulated systematically, gradually, and continuously.
Keywords: education, secondary education, free education, compulsory education, legal technique, self-government of higher educational institutions, right to self-government, academic freedom, research freedom, the Education Code